Common versus noble Bacillus subtilis differentially responds to air and argon gas plasma. Issue 17 (7th August 2013) - Winter, Theresa; Bernhardt, Jörg; Winter, Jörn; Mäder, Ulrike; Schlüter, Rabea; Weltmann, Klaus‐Dieter; Hecker, Michael; Kusch, Harald
<x xml:space="preserve">Abstract</x> The applications of low‐temperature plasma are not only confined to decontamination and sterilization but are also found in the medical field in terms of wound and skin treatment. For the improvement of already established and also for new plasma techniques, in‐depth knowledge on the interactions between plasma and microorganism is essential. In an initial study, the interaction between growing Bacillus subtilis and argon plasma was investigated by using a growth chamber system suitable for low‐temperature gas plasma treatment of bacteria in liquid medium. In this follow‐up investigation, a second kind of plasma treatment–namely air plasma–was applied. With combined proteomic and transcriptomic analyses, we were able to investigate the plasma‐specific stress response of B. subtilis toward not only argon but also air plasma. Besides an overlap of cellular responses due to both argon and air plasma treatment (DNA damage and oxidative stress), a variety of gas‐dependent cellular responses such as growth retardation and morphological changes were observed. Only argon plasma treatments lead to a phosphate starvation response whereas air plasma induced the tryptophan operon implying damage by photooxidation. Biological findings were supported by the detection of reactive plasma species by optical emission spectroscopy and Fourier transformed infrared spectroscopy measurements.